Identification Public Speaking Abilities in Online Classrooms Based on Class Observations and Students' Perceptions - Witma Novita Atnur; Erlia Utami Panjaitan; Rahmi Syafriyeti; Fitri Endang Srimulat; Syahraini Ritonga (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on classroom observations and students' views of their experiences, this study intends to evaluate the use of public speaking abilities in online courses. The Exploratory Sequential Mixed Design research approach was adopted, and 85 students participated in this study. The findings indicate that bodily content and visual cues are significant while speaking in public. The survey findings showed that participants did not want to attend online because they were on camera and had restricted screen display. There was also no difference in the substance of online and offline presentations, even though the visual component was thought to be the most beneficial and powerful in online presentations for attracting attention. An online public speaking course covering the visual message area in depth is also essential.